2022
DOI: 10.3390/medicina58101494
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miR-375-3p, miR-210-3p and Let-7e-5p in the Pathological Response of Breast Cancer Patients to Neoadjuvant Therapy

Abstract: Background and Objectives: Prediction of response to therapy remains a continuing challenge in treating breast cancer, especially for identifying molecular tissue markers that best characterize resistant tumours. Microribonucleic acids (miRNA), known as master modulators of tumour phenotype, could be helpful candidates for predicting drug resistance. We aimed to assess the association of miR-375-3p, miR-210-3p and let-7e-5p in breast cancer tissues with pathological response to neoadjuvant therapy (NAT) and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Oncogenic activity has been reported for this miRNA in the progression of lung and endometrial carcinoma (Han et al 2020;Dai et al 2022). On the other hand, in a study, it was reported that the desired pathological response was achieved with high expression of miR-210-3p in breast cancer (Lisencu et al 2022). These studies collectively reported the different activities of miR-210-3p in different cancer types.…”
Section: Discussionmentioning
confidence: 97%
“…Oncogenic activity has been reported for this miRNA in the progression of lung and endometrial carcinoma (Han et al 2020;Dai et al 2022). On the other hand, in a study, it was reported that the desired pathological response was achieved with high expression of miR-210-3p in breast cancer (Lisencu et al 2022). These studies collectively reported the different activities of miR-210-3p in different cancer types.…”
Section: Discussionmentioning
confidence: 97%
“…More and more ncRNA have been cataloged and connected to the prediction of treatment response in eBC [183][184][185]. However, low sensitivity and low specificity of detection techniques limit miRNA analysis, and new methods are under development.…”
Section: Non-coding Rnas: Mirna and Circrnamentioning
confidence: 99%
“…For breast cancer, for example, Lisencu et al [ 5 ] tried to determine molecular predictive factors which are linked to the probability of obtaining a pathological response to neoadjuvant treatment. Selecting early those patients with the best chance of responding to a selective (and costly) therapy remains a challenging task.…”
mentioning
confidence: 99%